An experimental study on steel and Teflon squeeze film dampers - Asad A., Khalid; Abdulgani M., Albagul; Waleed Fekry, Faris; Godem A., Ismail (IOS Press, 2006)

(untitled)
In this paper, the vibration analysis on Teflon and steel squeeze film dampers has been carried out. At different frequency ranges, vibration amplitude and the resonance frequency are measured. The eccentricity ratio at resonance speed has been determined. Results show that the vibration amplitude of the steel damper is 10% less at resonance compared with the Teflon damper. On the other hand, saving weight of 36% has been achieved by using the Teflon damper. A rotor bearing system for vibration analysis has been designed and fabricated. The test rig consists of mild steel shaft with two supports, oil pressure gauge system and two self-alignment ball bearings fixed on each end support. Two squeeze film dampers are used at each of the rotor support ends. Teflon and steel squeeze film dampers (SFD) were fabricated and tested using turning machine. © 2006 - IOS Press and the authors. All rights reserved.